Strategi Penerapan Tariqah Mubasyarah Dalam Pembelajaran Bahasa Arab Tingkat Madrasah Ibtidaiyah - Halimah, Siti (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2022)
Arabic Language in Indonesia has an unavoidable importance in the lives of its Muslim citizens. Learning from early childhood, elementary to middle school then becomes important. This literature research intends to explore important strategies in learning Arabic at the primary school level. Tariqah mubasyarah learning strategy then becomes an alternative to be implemented in learning Arabic. Such learning needs to be balanced with the growth rate of madrasah ibtidaiyyah students.